Building bridges between university and community: The "Tuning for Good" extension project - Amianti, Samanda Bertipalha; Harger, Patrícia Helena Campestrini; Nagamatsu, Rosimeiri Naomi; Pires, Gisely Andressa; Oenning, Josiany; Pereira, Livia Marsari (Seven Editora, 2023)
"The Sintonia do Bem project" aimed to serve the institutions that welcome adolescents in the city of Apucarana, among them "CEPES" and Casa Lar. To this end, the project acted on two fronts: offering short courses, meeting the demands of the institutions; and packing bags and necessaires. The Sintonia do Bem project is in constant activity, and for its progress the main actors are the servers, administrative technicians and volunteer students. Participate in the project 15 students and 4 servers who donate their time and commitment to these institutions. The workshops are usually taught at the CEPES site and the UTFPR Apucarana van transfers the volunteers in the morning and afternoon. The products developed are made in the laboratories of the Fashion Design Technology course, usually with fabrics that come from donations from local companies. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-139